Design and fabrication of optimised ribbed concrete floor slabs using large scale 3D printed formwork - Burger, Joris; Huber, Tobias; Lloret-Fritschi, Ena; Mata-Falcón, Jaime; Gramazio, Fabio; Kohler, Matthias (Automation in construction, 2022)
[Display omitted] •Developed a design-to-fabrication workflow for optimised ribbed concrete floor slabs.•Fabricated an optimised 2.7×2.7m reinforced concrete floor slab.•Achieved a material reduction of up to 40% compared to a flat slab.•Demonstrated the potential of 3D printed formwork for ribbed concrete floor slabs. This paper describes the design, fabrication, and testing process of an optimised, reinforced concrete ribbed floor slab fabricated using robotically 3D printed formwork. The design of the floor slab is based on the alignment of ribs along the trajectories of the principal bending moments. A workflow is described that generates a rib layout based on structural analysis, which is used to create a three-dimensional model of the slab. A full-scale prototype is fabricated by using an industrial robotic arm with a pellet extruder mounted as an end effector to 3D print the formwork. Reinforcement is inserted and the formwork is cast using self-compacting concrete. The successful design, fabrication, and structural testing of the full-scale floor slab prototype showed that the described workflow is suitable for realizing material-optimised, ribbed reinforced concrete floor slabs using 3D printed formwork.